Experimental evolution under predation in P. fluorescens SBW25 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology & Genetics at Massey University, Auckland, New Zealand - Sadeghpour Golzar, Farhad (Massey University, 2022)
Predator-prey interactions are recognised to change the pace of evolution in microbial communities, but investigations into how selection for predation accelerates antagonistic behaviours, genomic evolution and the process of coadaptation are scarce. Here we performed a 20-day and an extended 90-day evolution experiment to investigate the adaptive traits that arise in prey bacterium Pseudomonas fluorescens SBW25 on solid media in the presence and absence of a wild Acanthamoeba sp. Coevolution led to bacterial diversity, resistance to predation in coevolved bacterial lineages and evolution of predators. We show evidence of reciprocal adaptation, strong phenotypic and genotypic parallelism among prey lineages undergoing predation. We observed evolution of new colony morphotypes such as Wrinkly Spreader, Volcano and Mountain. Evolved morphotypes conferred grazing resistance and an increase in relative prey fitness that resulted in increased encystment and reduced replication of the protozoan populations. Mutation profiles of the coevolved phenotypes were associated with altered gene function in amrZ, wspF, fadD1, fadD2 and putative hypothetical protein upstream of RND transporter. RNA sequencing results of the mutants also revealed a significant increase in the number of genes that up or downregulated while interacting with Acanthamoeba sp. We investigated the degree to which these mutations affect biofilm formation, capsulation, motility, mucoid and fatty acid degradation pathways. Some of these traits are associated with virulence in pathogenic organisms. We further found evidence of mutualisms where both prey and predator increased their survival relative to their respective ancestors. On the other side, we show promoted killing performance and higher generations upon feeding on WT bacteria in coevolved Acanthamoeba compared to their ancestors. Together, our findings demonstrate the emergence of divergent colony morphologies and molecular parallelism that arise as an adaptation to predation and notably affects the fitness and evolution of predators suggesting Red Queen co-evolutionary dynamics between predators and prey. These findings suggest that protozoan predation can profoundly influence the course of genetic and phenotypic evolution in short and long-time scales.
Keywords: Pseudomonas fluorescens; Acanthamoeba; Experimental evolution; Predation (Biology); 310704 Microbial genetics